Protocluster Detection in Mock Photometric Surveys - Araya, Pablo Andrés Araya (2020)
The progenitors of present-day galaxy clusters give important clues about the evolution of the large scale structure, cosmic mass assembly, and galaxy evolution. Simulations are a major tool for these studies since they are used to interpret observations of protoclusters that are detected as enhancements in the distribution of galaxies, and test evolutionary scenarios. In this MSc Dissertation, we introduce a set of protocluster-lightcones, dubbed PCcones. They are mock galaxy catalogs generated from the Millennium Simulation with the previous version of the L-GALAXIES semi-analytic model. These lightcones were constructed by placing a desired structure at the redshift of interest in the center of the cone and taking into account the observational constraints associated with a given survey. We show that photometric redshifts (photo-zs) obtained with PCcones are more accurate than those obtained directly with the Millennium Simulation. We determine the expected accuracy of protocluster detection using photo-zs in the z=1-3 range in the wide layer of HSC-SSP and the 10-year LSST forecast. With our technique, we expect to recover ~38% and 43% of all massive galaxy cluster progenitors with more than 70% of purity for HSC-SSP and LSST, respectively, at the z=1-3 redshift interval. Our results also indicate that the combination of observational constraints and photo-z uncertainties affects the detection of structures critically. This happens for both emulated samples. We also compare our mocks of the Deep CFHTLS at z <= 1.5 with observed cluster catalogs, as an extra validation of the lightcones and our methods. Here, we found that both distributions are consistent with each other. This indicates that with PCcones, we can reproduce satisfactorily observational results.